Construction of cultural heritage evaluation system and personalized cultural tourism path decision model: An international historical and cultural city - Shuangyu Zhang; Jiayi Lin; Zhaoxin Feng; Yang Wu; Qianyi Zhao; Shen Liu; Yanshen Ren; Houhua Li (Journal of Urban Management, 2023)
World cultural heritage (WHS) is of great significance to promoting the sustainable development of cities, and history culture is very important to achieve the goal of sustainable development. The purpose of this paper is to construct a cultural heritage evaluation system and to explore and optimize tourist routes. We take cultural heritage sites as the research object, and comprehensively use Analytic Hierarchy Process (AHP), Delphi method and fuzzy mathematics to establish a cultural heritage tourism resource evaluation system. According to the evaluation results and questionnaires, a decision-making system for cultural tourism route planning is established, and additional sites of Qin culture are found, and a complete Qin culture route is established to provide data and theoretical basis for Xi'an's perfect cultural tourism route. The traveling salesman problem is the most basic path problem. In this study, the ant colony algorithm is used to improve the model combined with the actual problem of Xi'an tourist routes, and the optimal solution of the cultural parade route is obtained. Xi'an authorities and managers can strategically use these findings to promote Xi'an as a green destination WHS.
Keywords: 710; Ant colony algorithm; Cultural tourism; Personalized route selection; TSP model; World heritage site